Integration ofGreen Design Strategies in Urban Design:A Case of Arba Minch City, Ethiopia - Geremew G, Mariam (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The importance of green infrastructure in urban area is to maintain climatic conditions,increase social and economic benefits of urban dwellers. Nevertheless, urbanization has destroyed urban green and open spaces and this create problem such as climate change, pollution, and alteration of natural systems on urban dwellers. This study is going to investigates green infrastructure for Arab Minch city using mixed methodology and surveying methods. The research was conducted to the whole town by taking 68 sample blocks and plots based on systematic random sampling.